A new efficient collaboration model for multi-echelon supply chains. (15th August 2019) - Shaban, Ahmed; Costantino, Francesco; Di Gravio, Giulio; Tronci, Massimo
Highlights: Supply chain collaboration affects considerably supply chain performances. We propose a new collaboration model (IS-OUT) for multi-echelon supply chains. The IS-OUT relies upon the ordering structure of the classical order-up-to policy. Simulation is adopted to investigate the value of IS-OUT in supply chains. IS-OUT is successful to improve the supply chain performances. Abstract: Extensive research has shown that collaboration has substantial impact on supply chains performance. However, most of previous research has focused on information sharing-based collaboration models that require considerable effort to be implemented, such as information exchange supply chain (IESC). This paper introduces a new efficient collaboration model (IS-OUT) for multi-echelon supply chains. The IS-OUT model relies upon the ordering mechanism of the classical order-up-to policy (OUT). In traditional supply chains (TSC), although OUT replenishment orders include two pieces of information: demand forecast and inventory position balance, they are transferred to upstream echelons as single-quantity orders. In IS-OUT, the order information is transferred to the upstream echelons as two component parts of information to provide better coordination in supply chains. In this paper, the mathematical formulation of IS-OUT is presented, and simulation is adopted to compare the performance of TSC, IS-OUT, and IESC under special conditions and assumptions, considering various performance metrics. Although the results indicate that IESC model offers higher performance mostly than IS-OUT, IS-OUT outperforms or at least is comparable with IESC under a few conditions. Since IS-OUT model is easier to implement than IESC, IS-OUT provides a compromise between extent and information sharing requirements, and performance efficiency. The results should help a decision maker to select the model that optimizes its operating environment.